Hemothorax: A Review of the Literature. Issue 1 (January 2020) - Zeiler, Jacob; Idell, Steven; Norwood, Scott; Cook, Alan
Abstract : Hemothorax is a collection of blood in the pleural cavity usually from traumatic injury. A chest x-ray has historically been the imaging modality of choice upon arrival to the hospital. The sensitivity and specificity of point-of-care ultrasound, specifically through the Extended Focal Assessment with Sonography in Trauma (eFAST) protocol has been significant enough to warrant inclusion in most Level 1 trauma centers as an adjunct to radiographs. If the size or severity of a hemothorax warrants intervention, tube thoracostomy has been and still remains the treatment of choice. Most cases of hemothorax will resolve with tube thoracostomy. If residual blood remains within the pleural cavity after tube thoracostomy, it is then considered to be a retained hemothorax (RH), with significant risks for developing late complications such as empyema and fibrothorax. Once late complications occur, morbidity and mortality increase dramatically, and the only definitive treatment is surgery. In order to avoid surgery, research has been focused on removing an RH before it progresses pathologically. The most promising therapy consists of fibrinolytic, which are infused into the pleural space, disrupting the hemothorax, allowing for further drainage. Although significant progress has been made, additional trials are needed to further define the dosing and pharmacokinetics of fibrinolytics in this setting. If medical therapy and early procedures fail to resolve the RH, surgery is usually indicated. Surgery historically consisted solely of thoracotomy but has been largely replaced in nonemergent situations by video-assisted thoracoscopy, a minimally invasive technique that shows considerable improvement in the patients' recovery and pain postoperatively. Should all prior attempts to resolve the hemothorax fail, then open thoracotomy may be indicated.